Characterization of the trunk neural crest in the bamboo shark, Chiloscyllium punctatum. Issue 14 (25th July 2013) - Juarez, Marilyn; Reyes, Michelle; Coleman, Tiffany; Rotenstein, Lisa; Sao, Sothy; Martinez, Darwin; Jones, Matthew; Mackelprang, Rachel; De, Maria Elena
ABSTRACT The neural crest is a population of mesenchymal cells that after migrating from the neural tube gives rise to structure and cell types: the jaw, part of the peripheral ganglia, and melanocytes. Although much is known about neural crest development in jawed vertebrates, a clear picture of trunk neural crest development for elasmobranchs is yet to be developed. Here we present a detailed study of trunk neural crest development in the bamboo shark, Chiloscyllium punctatum. Vital labeling with dioctadecyl tetramethylindocarbocyanine perchlorate (DiI) and in situ hybridization using cloned Sox8 and Sox9 probes demonstrated that trunk neural crest cells follow a pattern similar to the migratory paths already described in zebrafish and amphibians. We found shark trunk neural crest along the rostral side of the somites, the ventromedial pathway, the branchial arches, the gut, the sensory ganglia, and the nerves. Interestingly, C. punctatum Sox8 and Sox9 sequences aligned with vertebrate SoxE genes, but appeared to be more ancient than the corresponding vertebrate paralogs. The expression of these two SoxE genes in trunk neural crest cells, especially Sox9, matched the Sox10 migratory patterns observed in teleosts. Also of interest, we observed DiI cells and Sox9 labeling along the lateral line, suggesting that in C. punctatum, glial cells in the lateral line are likely of neural crest origin. Although this has been observed in other vertebrates, we are the first to show that the pattern is present in cartilaginous fishes. These findings demonstrate that trunk neural crest cell development in C. punctatum follows the same highly conserved migratory pattern observed in jawed vertebrates. J. Comp. Neurol. 521:3303–3320, 2013. © 2013 Wiley Periodicals, Inc.